Believing in Infinity: Exploring Students' Conceptions of Improper Integrals. Issue 5 (28th May 2023) - Zolt, Holly; Wrightsman, Elizabeth; Ford, Lucinda; Patterson, Cody L.
Abstract : We discuss student conceptions of improper integrals and infinity in the context of a second-semester calculus course (in a three-course sequence). Our observations stem from a sequence of activities used in an online course over a three-day period. Throughout the enactment of these activities, students are challenged to develop conceptions of improper integrals that are compatible with the conventions of the discipline, and they are forced to wrestle with their underlying beliefs about infinity, limits, and areas of unbounded regions.